2006
DOI: 10.1261/rna.2272306
|View full text |Cite
|
Sign up to set email alerts
|

Archaeology and evolution of transfer RNA genes in the Escherichia coli genome

Abstract: Transfer RNA genes tend to be presented in multiple copies in the genomes of most organisms, from bacteria to eukaryotes. The evolution and genomic structure of tRNA genes has been a somewhat neglected area of molecular evolution. Escherichia coli, the first phylogenetic species for which more than two different strains have been sequenced, provides an invaluable framework to study the evolution of tRNA genes. In this work, a detailed analysis of the tRNA structure of the genomes of Escherichia coli strains K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 47 publications
(53 reference statements)
4
55
0
Order By: Relevance
“…This is striking, given the differences in lifestyles, effective population sizes, generation times, ecological niches, metabolic routes, genomic GC, etc., that characterize the different micro-organisms. Withers et al (2006) found that for most of the tested genomes, CU frequencies matched more closely to the putative ancestral set of tRNA genes than to extant ones. Our results support this statement, which has important implications for understanding CU and tRNA coevolution.…”
Section: Discussionmentioning
confidence: 85%
“…This is striking, given the differences in lifestyles, effective population sizes, generation times, ecological niches, metabolic routes, genomic GC, etc., that characterize the different micro-organisms. Withers et al (2006) found that for most of the tested genomes, CU frequencies matched more closely to the putative ancestral set of tRNA genes than to extant ones. Our results support this statement, which has important implications for understanding CU and tRNA coevolution.…”
Section: Discussionmentioning
confidence: 85%
“…The number of tRNA genes present in the Salmonella reference genome is 85, representing 47 diferent tRNA molecules that together cover the 40 required anticodons [20]. These numbers can vary between genomes and serovars.…”
Section: Conserved Rnas Across 201 Salmonella Genomesmentioning
confidence: 99%
“…They are usually grouped in the genome within clusters (or operons in the case of microbial genomes), representing highly repetitive regions, causing genomic instability through illegitimate homologous recombination. In consequence, stable RNA families are rapidly evolving by duplication and loss [35,3,28].…”
Section: Evolution Of Stable Rna Gene Content and Organization In Bacmentioning
confidence: 99%
“…In parallel, gene losses through pseudogenization and segmental deletions, appear generally to maintain a minimum number of functional gene copies [5,9,10,12,16,22,25]. Transfer RNAs (tRNAs) are typical examples of gene families that are continually duplicated and lost [3,28,31,35]. Indeed, tRNA clusters (or operons in microbial genomes) are highly dynamic and unstable genomic regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation